Prognostic evaluation in head and neck cancer patients: a clinicoimaging tertiary care center study - Keerthika, N. Kavya; Veda, D. Sri; Prabhat, M. P. V.; Sarat, G.; Maini, Gunmeet (International Journal Of Community Medicine And Public Health, 2021)
Background: The occurrence of the head and neck cancers (HNC) is increasing day by day. These have been associated with multiple etiological factors, and early diagnosis has a prime role in the patient’s prognosis and overall survival. Prognostic evaluation in head and neck cancer patients utilizing clinical incidence and imaging outcomes. Methods: The study sample included 217 confirmed HNC patients’ data obtained from the tertiary cancer care centre were analysed to assess the prognosis and be subjected to statistical analysis. Results: Out of all HNC, cancer pertaining to the lip and oral cavity was the most common variety with 65.89% and most of the HNC occurred in men of about 97%, suggesting a strong association with adverse oral habits. Conclusions: We conclude that the current scenario of HNC’s progression and treatment modalities in Andhra Pradesh were in comparison to the World Health Organization (WHO) data suggests an increase in the awareness of the etiological factors and the disease progression. Though various advanced imaging and treatment modalities are available, the patients’ prognosis is untethered due to low socio-economic status in this region.